2000
DOI: 10.1097/00000658-200010000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Complete Repair of Tetralogy of Fallot in the Neonate

Abstract: Complete repair of TOF in the neonate is associated with excellent intermediate-term survival. Although the reoperation rate is significant, this is to be expected with the complex right ventricular outflow tract and pulmonary artery anatomy seen in symptomatic neonates and the need for conduit replacement in patients with TOF with pulmonary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 16 publications
6
111
2
1
Order By: Relevance
“…In large pediatric cardiac centers in North America, however, postoperative mortality after complete repair of many congenital heart defects in neonates is currently Ͻ5%. [17][18][19][20] Therefore, if a general neonatal cardiac surgery population is studied, enrolling sufficient patients to achieve adequate statistical power using mortality as the primary efficacy end point will be problematic, even in multicenter studies. In contrast, early mortality after initial palliation of the complex single ventricle lesion hypoplastic left heart syndrome using the modified Norwood procedure is ϳ10% to 15% in larger centers that are experienced with this procedure.…”
Section: Study-design Issuesmentioning
confidence: 99%
“…In large pediatric cardiac centers in North America, however, postoperative mortality after complete repair of many congenital heart defects in neonates is currently Ͻ5%. [17][18][19][20] Therefore, if a general neonatal cardiac surgery population is studied, enrolling sufficient patients to achieve adequate statistical power using mortality as the primary efficacy end point will be problematic, even in multicenter studies. In contrast, early mortality after initial palliation of the complex single ventricle lesion hypoplastic left heart syndrome using the modified Norwood procedure is ϳ10% to 15% in larger centers that are experienced with this procedure.…”
Section: Study-design Issuesmentioning
confidence: 99%
“…Currently, corrective surgery is typically performed in the first year of life. 39 With good surgical results, survival and quality of life have been excellent. In a retrospective analysis from the Mayo Clinic, 86% of patients were alive at 32 years, 40 and in a series of 151 patients from Toronto, Canada, 41 94% were in New York Heart Association functional class I.…”
Section: "Natural History" After Surgical Intervention For Tetralogymentioning
confidence: 99%
“…Kirklin et al and Katz et al reported that the mortality risk was increased by 2.5 and the re-operation risk was increased by 7.3-fold when RV/LV pressure ratio is > 0.85 [11,20]. Hirch et al also reported that the re-operation risk is increased when the RV/LV pressure ratio is > 0.7 [21]. In the present study, we aimed to keep the RV/LV pressure ratio < 0.7 in both treatment groups.…”
Section: Discussionmentioning
confidence: 98%